2021
DOI: 10.1097/fjc.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of Sacubitril/Valsartan: A Meta-analysis of Randomized Controlled Trials

Abstract: This review aimed to summarize the adverse events (AEs) reported during the use of sacubitril/valsartan versus angiotensin converting enzyme inhibitors (ACEI)/angiotensin II receptor blocker (ARB). Studies containing safety outcomes or AEs during the use of sacubitril/valsartan versus ACEI/ARB were retrieved from the MEDLINE, Embase, and Cochrane Library databases and clinical trials. From the selected studies, the pooled risk ratios with 95% confidence intervals of dichotomous outcomes were assessed by a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(104 reference statements)
1
5
0
Order By: Relevance
“…The meta-analysis showed that LCZ696 was superior to ACEis and ARBs in improving the overall mortality, rate of hospitalizations for HF, decline in renal function, and reduction in NT-proBNP levels in patients with HF. These results were consistent with those in Huang et al’s study, [ 27 ] in which it was reported that compared with ACEI/ARB, LCZ696 decreased the risk of death, discontinuation due to AEs, and decline in renal function. Moreover, Kang et al [ 28 ] reported that LCZ696 significantly increased the estimated glomerular filtration rate ( P = .02) and reduced the NT-proBNP level ( P < .001) compared with irbesartan, valsartan, and enalapril.…”
Section: Discussionsupporting
confidence: 93%
“…The meta-analysis showed that LCZ696 was superior to ACEis and ARBs in improving the overall mortality, rate of hospitalizations for HF, decline in renal function, and reduction in NT-proBNP levels in patients with HF. These results were consistent with those in Huang et al’s study, [ 27 ] in which it was reported that compared with ACEI/ARB, LCZ696 decreased the risk of death, discontinuation due to AEs, and decline in renal function. Moreover, Kang et al [ 28 ] reported that LCZ696 significantly increased the estimated glomerular filtration rate ( P = .02) and reduced the NT-proBNP level ( P < .001) compared with irbesartan, valsartan, and enalapril.…”
Section: Discussionsupporting
confidence: 93%
“…Several other studies supported that sacubitril/valsartan was associated with the reduction of the apnea burden in patients with HFrEF and the improvement of blood glucose control in patients with CHF and diabetes ( 14 , 15 ). In terms of safety, sacubitril/valsartan has a lower risk of renal impairment and severe hyperkalemia, and does not increase the risk of severe angioedema compared with ACEI/ARB, but the risk of hypotension is slightly higher ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs serve as the foundations of pharmacotherapy for patients with HFrEF. Therefore, it is recommended that an ACE-I or ARB is replaced by sacubitril/valsartan in ambulatory patients with HFrEF, who remain symptomatic despite optimal medical treatment ( 1 - 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 2021 ESC published guidelines recommends the use of ARNI as a replacement for ACE-I in suitable patients who remain symptomatic on ACE-I, beta-blocker, and MRA therapies; however, an ARNI may be considered as a first-line therapy instead of an ACE-I - (Class of Recommendation 1B) in reducing the risks of cardiovascular death and hospitalization ( 1 ). In addition, a meta-analysis provided evidence that sacubitril/valsartan had fewer drug-risks compared with ACEIs/ARBs, such as angioedema, hyperkalemia, cough, dizziness, renal dysfunction and arterial hypotension ( 6 , 7 , 10 - 13 ).…”
Section: Discussionmentioning
confidence: 99%